Gaussian Integers and Applications - MAOUCHE, FATIMA; LADJELAT, LAHCENE: Supervisor. (Mohamed Boudiaf University of M’sila, Faculty of Mathematics and Informatics, Departement of Mathematics, 2024)
The goel of this work is to study some properties of the ring of Gaussian Numbers Z[i]: complex numbers whose real and imaginary parts are both integers (in z). These properties are related to the algebraic structure of the ring: construction, Euclidean algorithm, gcd, lem, unique factorization. Finaly, we mention some of their applications in Number Theory, geometry, and Analysis
Keywords: Ideal; the ring of gaussian integers; TECHNOLOGY::Engineering physics::Other engineering physics